Analysis of Transjakarta Bus Stop user Services by IoT at Dukuh Atas Dua - Setiawan, Chrisna; Syaiful, Syaiful; Chayati, Nurul; Wardhani, Asri Kusuma; Ngadimo, Ngadimo (ASTONJADRO, 2026)
Transportation is an essential means to support the success of national development, especially to support the economic sector. Transjakarta Bus is a bus rapid transit (BRT) transportation system. Transjakarta passengers continue to increase over time, the highest point in the number of Transjakarta passengers occurred in April 2023, which was 33,500 people. During the transition period, the existing facilities provided at the Dukuh Atas Dua Bus Stop for Transjakarta Bus passengers had a positive impact, passengers felt comfortable with the bus stop facilities that were much more complete than before. Transjakarta Bus user service level at the Dukuh Atas Dua Bus Stop obtained several characteristics. Starting from the characteristics of male gender, it is more dominant at 56% or as many as 224 respondents. While based on user characteristics based on age, namely 30 years and under, it is more dominant at 45% or as many as 179 respondents. Furthermore, based on undergraduate education, it is more dominant at 38% or as many as 150 respondents. Analysis of user responses to the Transjakarta Bus Stop service at Dukuh Atas Dua obtained Reliability indicators of 52.3% or with a score of 4, Responsiveness 52.5% or with a score of 4 and Tangibility 54.0% or with a score of 4 with all respondents stating that users strongly agree. This study discusses IoT implementation at Dukuh Atas 2 TransJakarta Bus Stop to improve transportation efficiency, safety, passenger comfort, and smart city integration.